SURGICAL TREATMENT FOR ALZHEIMER’S DISEASE: A NEW PERSPECTIVE - Alves Milhomens, Isabela; Moreira Andrade, Gustavo; José da Silva, Ledismar (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2024)
Deep Brain Stimulation (DBS) is a safe and promising neurologic technique for the treatment of Alzheimer’s disease (AD), a neurodegenerative condition prevalent in elders. This paper reviews the application of the DBS in specific targets in the brain, such as the fornix, the entorhinal cortex (EC), the nucleus basalis of Meynert (NBM), and the thalamic nuclei. The studies were analyzed and it showed that DBS can make the brain metabolism better, reduce inflammation, and stabilize the cognitive downstage, resulting in better quality of life for the patients. Although these results sound very promising, the variety of the answers suggests the need for personalizing the stimulation parameters and more research to optimize this therapeutic approach.